The city centre as an age-friendly shopping environment: a consumer perspective - Kohijoki Anna-Maija; Koistinen Katri (Cambridge University Press, 2025)
Urban population ageing has significant implications for city centres catering for an
increasing number of older consumers. To guide world cities on taking action in response
to population ageing, the World Health Organization (WHO) has addressed the universal
features of the age-friendly city. This study applies the WHO guideline to the context of
shopping. With an emphasis on older consumers, the perceptions of the city centre as a
physical and social shopping environment are studied. Using a qualitative content analysis,
older consumers’ perceptions (focus-group participants aged 64–94) are analysed
based on the age-friendly city features. The perceptions are compared with those of
younger consumers (qualitative-survey respondents aged 21–41). The study confirms
the significance of older city shoppers, and suggests their needs and wants should be
taken into account in urban development projects. The older consumers differ from
younger consumers in their city-shopping behaviour and perceptions in many respects.
The age groups highlighted the same themes, but mainly with dissimilar content. This
indicates that measures to develop a city centre friendlier to older consumers also benefit
their younger counterparts, but for different reasons. It is necessary to understand this disparity
to create a city-centre shopping environment that is friendly for different ages. The
study offers new perspectives on responding to the challenges that consumer ageing poses
to Western cities.